The Impact of Profitability, Liquidity, and Dividend Policy on Stock Prices of Mining Companies Listed on The Indonesia Stock Exchange in The Period of 2017 to 2021 - Regina Anastasia (Journal of E-business and Management Science, 2023)
This research aims to determine the effect of profitability, liquidity, and dividend policy on the share prices of mining companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. The research method is quantitative, using a literature study of information in financial reports with a total sample of 14 companies processed using SPSS version 27. The results of this research show that profitability, liquidity, and dividend policy simultaneously (F test) have an influence on stock prices. Meanwhile, partially (T-test), profitability and liquidity influence stock prices, and dividend policy has no effect on stock prices.